PENGARUH DIVERSIFIKASI SUMBER PENDAPATAN TERHADAP KETAHANAN EKONOMI KELUARGA PETANI DI KAMPUNG MERANCANG ULU - RESTI AYU SAFITRI (ECO-BUILD, 2026)
Agriculture remains the main source of livelihood for a large share of Indonesia's rural population, yet farming households are highly exposed to income risks such as commodity price fluctuations, climate variability, crop failure, and limited access to markets and capital. Income diversification is widely regarded as a coping strategy to reduce this vulnerability, although its actual effect on household welfare varies across contexts. This study examines the effect of income source diversification on the economic resilience of farming families in Kampung Merancang Ulu, Berau Regency. Using a quantitative approach, primary data were collected through questionnaires from 72 respondents selected through a saturated sampling technique, and analyzed using simple linear regression, Pearson product-moment correlation, and t-test with the aid of SPSS. The results show a regression equation of Y = 18.535 − 0.165X, indicating that income diversification has a negative and statistically significant effect on family economic resilience (t = −3.353; sig. = 0.001 < 0.05), with a Pearson correlation coefficient of −0.372, reflecting a weak-to-moderate negative relationship. These findings suggest that diversification practiced by farmers in Kampung Merancang Ulu remains largely subsistence-oriented, undertaken mainly as supplementary work without adequate capital, technology, or skills, and therefore adds to household labor burden rather than improving welfare. The study concludes that income diversification is only effective as a resilience strategy when supported by external factors such as market access, training, capital assistance, and appropriate government policy, and recommends capacity building, continued extension services, and access to financing to help farming households diversify more strategically and sustainably